Analysis of the Influence of Brand Loyalty, Brand Association, Brand Awareness, Perceived Quality, and Country Image on Purchase Intention at Uniqlo Brand in Batam City - Ricardo, Teddy; Laulita, Nasar Buntu (Jurnal Maksipreneur, 2025)
The fashion industry, with various international brands, is established in Batam City. With so many international brands, there is very tight competition among these brands, so a right strategy is needed to deal with this competition. This study aims to analyze the influence of brand loyalty, brand association, brand awareness, quality perception, and country image on significant purchase intention. The object of this research is one of the international brands in Batam City, namely Uniqlo. Sampling in this study was conducted using the purposive sampling technique, and a total of 411 respondents were included in the analysis. The data in this study were obtained by distributing questionnaires using Google Forms, which were completed by respondents from Batam who had made purchases at Uniqlo. The data is processed through the SmartPLS 3.0 program using PLS. The study's results indicated that brand loyalty, brand awareness, and perceived quality had a significant positive effect on purchase intention, whereas purchase intention was not influenced by brand association or country image.